A Person-Centered Examination of Motivational Profiles and Employment Preferences Across Age Groups - Wang, Daisy; Wang, Zheni (Academy of Management Proceedings, 2026)
This cross-sectional study examines how age-group differences in work motivation and basic psychological needs relate to preferences between self- and wage-employment. Drawing on Self-Determination and Lifespan Development Theories, age groups are conceptualized as life-stage categories rather than birth cohorts, and motivational profiles are compared in the post-COVID US labor market. Online survey data were collected from 1,484 adult Americans across five age groups, from Gen Z to Traditionalist. Multi-group CFA for measurement invariance, ANOVA, latent mean comparisons, and latent profile analysis with distal outcome comparisons were performed. Results indicated significant, albeit small, age-group differences in employment preferences and motivational constructs. Gen Z-young adults reported relatively stronger preference for self-employment than older age-groups, whereas Gen Y (Millennials), early to mid-career, exhibited the highest autonomous motivation, the lowest amotivation, and greater satisfaction of autonomy and competence needs at work. Five distinct motivational profiles were identified from latent profile analyses; low-intensity and controlled–amotivated profiles were most strongly associated with a preference for self-employment, whereas a high-involvement yet conflicted profile showed the strongest preference for wage-employment. Younger participants, particularly Gen Z and Gen Y, were more likely to fall into globally elevated and psychologically complex profiles. Overall, the findings suggest that age-linked life stages are associated with nuanced motivational configurations that only modestly translate into employment preferences, highlighting the value of developmentally sensitive, person-centered approaches to understanding contemporary work, employment preferences, and entrepreneurial orientations.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Human Resources; Paper - Abstract Only; dept.mgt

The Conditional Value of Consumer Satisfaction: Innovation Choice Under Economic Recession - Yoo, Jae Kyun; Lee, Minjae (Academy of Management Proceedings, 2026)
Economic recessions reshape consumer expectations and amplify scrutiny, altering how firms’ capabilities translate into performance. This study examines how recession-driven shifts in consumer expectations intensify the vulnerability of firms with high preexisting consumer satisfaction and how their innovation choices shape the extent to which this capability becomes a liability. We argue that recessions heighten negative reactions to perceived performance deviations, making high pre-recession satisfaction—typically a strategic strength—especially vulnerable. Using data from the U.S. automobile industry spanning the 2008 financial crisis, we find that consumer satisfaction declines significantly during recession and that firms with higher preexisting satisfaction experience disproportionately larger losses. We further demonstrate that innovation strategy plays a decisive moderating role: incremental product redesigns, which preserve familiarity and signal stability, mitigate the recession penalty for high-satisfaction firms, whereas new product introductions do not offer comparable protection. The study provides a theoretical account of how economic downturns can invert the value of demand-side capabilities and identifies conditions under which incremental innovation outperforms more transformative approaches. Managerially, the findings offer guidance on how firms can align innovation portfolios with shifting consumer psychology to protect reputational assets and sustain performance during an economic disruption.
Keywords: AOM Annual Meeting Proceedings 2026; AOM Philadelphia 2026; Paper - Abstract Only; Technology and Innovation Management; dept.mgt

The future is here! Recognizing the need to revitalize and transform business education via digital integration - Philip, Jestine; Schmidt, Gordon B.; Simha, Aditya; Rosen, David (Business Horizons, 2026)
Business education is undergoing rapid transformations thanks to advancements in emerging technologies. Business school leaders are engaging in identifying approaches to revitalize business education, preparing students to succeed in a technologically advancing workplace. Primarily anchored in the concept of digital transformation, our article provides practical guidance to help business schools integrate artificial intelligence (AI) into their curricula and infrastructure, benefiting students, faculty, administration, and leadership. We offer a roadmap that lays out current industry trends and articulates pertinent action items, related cost efforts, and associated benefits for business education. This article positions business schools to instill a human-AI augmentation mindset in students, faculty, staff, and leadership that prepares them to work with ever-changing technologies. Regularly revising business course curricula to stay aligned with evolving industry needs is key to providing topical content and meaningful skill development opportunities for students. We argue that these efforts directly enhance student employability and learning, better preparing students to succeed in the increasingly technology-enabled workplace. © 2026 Kelley School of Business, Indiana University. Published by Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Artificial intelligence (AI); Business schools; Digital transformation; Generative AI (GenAI); Human-AI augmentation mindset; dept.mgt

From fragmentation to integration: finding the psychological and instrumental common ground for algorithmic management and marketing - Wang, Zheni; Wang, Emma; Zhu, Guorong (SSRN Electronic Journal, 2026)
Keywords: Common ground; Corporate governance; Fragmentation (computing); Service (business); Spillover effect; Stakeholder; Stakeholder analysis; Stakeholder theory; dept.mgt; dept.mrk

How Do Firms Build Green Supply Chain Learning System? A Theoretical Framework and Directions - Birasnav, M.; Han, Seungmin; Arora, Ridhi; Sangar, Ruby (Corporate Social Responsibility and Environmental Management, 2026)
Keywords: Green innovation; Mechanism (biology); Perspective (graphical); Resource (disambiguation); Supply chain; Supply chain management; Workforce; corporate social responsibility; dept.mgt; environmental performance; exploitation; exploration; green supply chain; leadership; learning system

Framing the future: how museums shape sustainability mindsets in business education - Yang, Charlie; Ivanova, Ekaterina; Ivanova, Maria (The Power of Arts-Based Pedagogies: Transforming Mindsets to Shape Our Future, 2026)
Recent research proposes that arts-integrated teaching approaches in business education can nurture students' aesthetic sensitivity and emotional capacities, such as self-awareness and empathy. In this chapter, we examine the pedagogical possibility of art appreciation in art museums as a consciousness-raising practice, especially for the sake of cultivating business students' environmental awareness in two different contexts. We have analyzed American and Russian students' reflective essays based on their museum visits in order to explore how business students make sense of their aesthetic experiences and how art appreciation helps them to develop their sustainability mindset in a creative learning space. Through attentive viewing of the works of art, students have learned some key insights from their aesthetic appreciation at art museums. These insights not only facilitated honing their emotional skills, but also deepened their environmental awareness and heightened their sense of personal empowerment to act upon these newly acquired insights and values ensuing from art appreciation. After identifying six key themes extracted from both groups of students' essays based on their museum learning, we further discuss the pedagogical implications of contemplative art appreciation in museums as a means of contributing to more innovative and sustainable management education. © 2026 selection and editorial matter, Ekaterina Ivanova, Isabel Rimanoczy and Divya Singhal; individual chapters, the contributors.
Keywords: dept.mgt

Quality management and safety performance: the influence of ethical leaders among public sector employees - Birasnav, M.; Dahiya, Rinki; Dalpati, Avadhesh (The TQM Journal, 2026)
Keywords: Ethical leadership; Incentive; Job satisfaction; Motivation for QM implementation; Perceived safety performance; Public sector; Quality (philosophy); Structural equation modeling; Survey data collection; Test (biology); Work (physics); dept.mgt